Dose Ginger Have Preventative Effects on PONV-Related Eye Surgery? A Clinical Trial - Sedigh Maroufi, Shahnam (Anesth Pain Med, 2019)
BACKGROUND: Postoperative nausea and vomiting (PONV) is considered a common complication of anesthesia, which, particularly in eye surgery, may exert pressure on stitches and open or leak the surgical wound, leading to bleeding. OBJECTIVES: We aimed to study the effect of ginger on PONV and changes in vital signs after eye surgery. METHODS: In this triple-blind randomized controlled trial, 120 candidate patients for eye surgery were divided into group A (n = 40) and group B (n = 40). Patients in group A received the capsules of ginger 1 g while patients in group B received a placebo one hour before the procedure with 30 mL water. The incidence of nausea and the frequency of vomiting were evaluated at 0, 15, 30 minutes, and 2 hours after the operation. Also, the vital signs of the participants were recorded at certain times. RESULTS: The results demonstrated a statistically significant difference in the frequency of nausea between group A and group B (P < 0.05). The severity of nausea was lower in group A than in group B immediately and 2 hours after recovery (P < 0.05). The incidence of vomiting was significantly lower in group A than in group B (P < 0.05). The vital signs were not significantly different between group A and group B (P > 0.05). CONCLUSIONS: Ginger was effective in the prevention of PONV after eye surgery but had no impact on vital signs. Hence, ginger is proposed to use as a low-cost, prophylactic measure for PONV reduction.